PENGARUH PEMBERIAN GARAM BERIODIUM TERHADAP KADAR TIROKSIN PADA IBU USIA SUBUR DI DAERAH ENDEMIK DEFISIENSI IODIUM - Budiman, Basuki; -, Komari; -, Saidin (PERSATUAN AHLI GIZI INDONESIA, 2005)
THE EFFECT OF IODIZED SALT INTERVENTION ON THYROXINE OF CHILDBEARING AGE MOTHERS IN ENDEMIC IODINE DEFICIENCY AREAThe national evaluation on implementation of Iodized salt indicate an excess dietary intakes of iodine. It is a consequence of the correction of iodine deficiency. However there is no confirmation of the adverse effect to the excess in Indonesia. Our aim is to elaborate whether the excess of iodine consumption affect serum thyroxine. We supplied 50-ppm iodized salt to 82 mothers at childbearing age’s family every two weeks for three months. We suggest the mothers used the supplied iodized salt for family consumption only and not used the salt for any other purposes such as cattle feeding. Mother’s blood drawn before and after intervention. Urine iodine exretion (UIE) were collected from school age children of participant family. The study revealed that three month-iodized salt intervention increased median UIE by 18.4 % and serum thyroxine level by 36.5 %. The number of children being at risk for hyperthyroidism were constributed from normal and deficit range level at initial study by 62,5 % and 41.7 % respectively. The number of mothers being thyroxine excess were 22.2 and 22.7 % respectively. We conclude that the level of iodine consentration in salt at 50 ppm is high and suggest that consentration should be lowered.Keywords: EIU, at risk for hyperthyroidism, thyroid hormone excess.mother at child bearing age.